DIALOGUE AND CONVERSATION: Humean Way of Doing Philosophy - Mariadas, Jose (Journal of Dharma, 2017)
David Hume’s philosophy has invited often a lot of criticism because of its abstruse style and therefore earned very strong criticism from all the corners. In spite of the fact that he is often accused of sophism, inconsistency and contradictions his arguments are demanding and provoking and philosophers like Immanuel Kant acknowledges that "I freely admit that the remembrance of David Hume was the very thing that many years ago first interrupted my dogmatic slumber and gave a completely different direction to my researches in the field of speculative philosophy." This paper argues that a rereading of Hume’s philosophy is worth doing because the traditional understanding fails to explore the rich possibilities of Humean philosophy. It is argued that without analysing his concepts of philosophy, truth and method of doing philosophy we cannot do justice to Hume’s philosophy. This paper tries to show that Hume’s concept of dialogical and conversational style of truth seeking is something very relevant, unique and promising.